Indonesian Pre-Service EFL Teachers’ Perceptions and Expectations of Generative AI in Teacher Education: A Phenomenological Study - Zainal ꞌArifin; Atin Kurniawati (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
The rapid growth of Generative Artificial Intelligence (GenAI) in education has created an urgent need to understand how future teachers perceive its benefits, risks, and required skills, especially in the Indonesian context. This current study aims to explore Indonesian EFL pre-service teachers’ perspectives toward GenAI and their expectations regarding educational content related to GenAI at teacher training programs. Employing a qualitative approach with phenomenology design, the data in this study were obtained through reflective writings and semi-structured interviews involving pre-service teachers from the English Language Education Department at an Indonesian state Islamic university. The findings of thematic analysis reveal that they perceive GenAI benefits teachers by serving as a brainstorming partner for designing learning activities and saving time, while also supporting students through personalized learning experiences and instant feedback that can enhance their performance. Despite its advantages, GenAI poses challenges such as its occasional unreliability for teachers and potential overreliance that may hinder original thinking and professional growth. Meanwhile, overreliance on AI could lower students’ interaction and critical thinking, increase plagiarism risk, and foster the perception that AI is more capable than teachers. Teacher training programs are supposed to address it by focusing on three aspects, namely GenAI literacy, pedagogical knowledge, and ethical considerations. The findings imply that teacher education programs must systematically integrate GenAI literacy, pedagogical application, and ethical guidance to develop competence in leveraging AI effectively while maintaining critical thinking, thoughtful instructional autonomy, and responsible professional practice.